Chondroitin sulfate anchored biodegradable nanoparticles: Design, synthesis, and In-vitro anti-tubercular efficacy. (March 2023) - Mazahir, Farhan; Sahoo, Rakesh Kumar; Gupta, Umesh; Yadav, Awesh K.
Abstract: The present research aims to prepare Bedaquiline fumarate (BDQ) encapsulated plain and chondroitin sulfate (CS) modified Poly (Lactide-co-glycolide) (PLGA) nanoparticles (NPs) (BCPNs) for the treatment of multi-drug resistant Tuberculosis (MDR-TB). First, BDQ-loaded PLGA NPs (BPNs) were prepared by a solvent evaporation method and further coated with CS to obtain BCPNs. The coating of CS on the surface of NPs was confirmed by IR and NMR spectroscopy and with the help of zeta potential. The particle size, zeta potential, and polydispersity index of BPNs and BCPNs were found 216 ± 37.11 nm and 434 ± 11.33 nm, + 15 ± 2.4 mV and + 5 ± 2.1 mV and 0.224 ± 0.34 and 0.297 ± 0.26, respectively. High-resolution transmission electron microscopy (HR-TEM) was utilized to observe the surface morphology of BCPNs. The differential scanning calorimetry (DSC) confirmed the crystalline character of BDQ, and DSC analysis of BDQ-loaded NPs showed molecular dispersion of BDQ. The in-vitro BDQ release data of plain (BPNs) and CS-modified BCPNs, showed extended drug release up to 48 hrs. The results of the in-vitro hemolytic study revealed that BCNPs showed higher biocompatibility than BNPs and the control groups. The anti-TB efficacy of BDQ-loaded BPNs and CS-modified BCPNs against M. tuberculosis (H37Rv ATCC 27294), M. abscessus (ATCC 19977), M. tuberculosis abscessus (ATCC 6841), and M. chelonae (ATCC 35752) stains was tested with the help of Microplate Alamar Blue Assay (MABA). Also, the minimum inhibitory concentrations (MIC) of BPNs and BCPNs were determined against several strains of mycobacteria, bacteria and fungus. The in-vitro therapeutic efficacy data suggested the effective role of BPNs, and BCPNs in the eradication of MDR-TB. Moreover, BDQ-carrying BPNs and BCPNs could be used as a formulation for the eradication of MDR-TB. Graphical Abstract: ga1